"Corpses … Coast to Coast!" Trauma, gender, and race in 1950s horror comics. Issue 9 (September 2017) - Smith, Philip; Goodrum, Michael
Abstract: During the 1950s, a moral panic around youth culture and delinquency dominated the contemporary imagination. Rock n' roll and the new wave of youth‐focused films seemed to critics to posit an alternative culture antagonistic to that of older generations. One cultural form sparked particular censorious intent: the horror comic book. Many critics of the 1940s and 1950s dwelt obsessively on the impact of horror comics on youthful readers. The culmination of this movement was the 1954 Senate Subcommittee Hearings on Juvenile Delinquency, which resulted in the implementation of a harsh new self‐regulatory comics code and the end of the horror and crime genres. In this study, we argue that rather than (or perhaps as well as) promoting juvenile delinquency, horror comics served an important social function in that they presented a challenge to the dominant culture in cold war America. They corroborated the veteran experience; questioned faith in science and industry; recognised women as victims of war; and embodied, on occasion, many of the themes of the early Civil Rights movement. It was because of these countercultural impulses that the horror genre in comics was, ultimately, brought to an untimely end.